Transformational Leadership in Islamic Educational Institutions and Impact on Organizational Performance - Nur Efendi (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2023)
This study investigates the role of transformational leadership in shaping organizational performance within an Islamic educational institution, focusing on SMPI Sunan Gunung Jati. The research examines how leadership practices influence organizational processes, teacher performance, and institutional outcomes. A qualitative case study design was employed to explore in-depth perspectives from the principal, teachers, and administrative staff. Data were collected through semi-structured interviews, observations, and document analysis, then analyzed using thematic analysis. The findings indicate that transformational leadership fosters a shared vision, strengthens professional commitment, and supports continuous improvement within the institution. Leadership practices such as motivation, individualized support, and collaborative engagement contribute to enhanced instructional quality and more effective organizational processes. Organizational performance is reflected in improved teaching practices, increased student engagement, and structured institutional management. The study also reveals a dynamic interaction in which leadership influences teacher behavior, organizational processes support performance, and outcomes provide feedback for leadership refinement. These findings highlight the significance of transformational leadership in sustaining organizational effectiveness within Islamic educational contexts.